PROJECT MANAGEMENT IN HEALTHCARE: A CASE STUDY FOR PATIENT FLOW EVALUATION IN AN EMERGENCY ROOM USING FUZZY CPM AND FUZZY PERT - Gul, Muhammet; Guneri, Ali Fuat; Gunes, Gizem (YILDIZ TECHNICAL UNIV, 2017)
An ideal healthcare system is considered as a system that provides the most quality service level, lower costs and unlimited access. Any delay in patient flow may result in undesired consequences and losses in healthcare facilities such as hospitals and their sub units. Project management is defined as application of techniques to project activities to meet the project requirements. It has techniques that can help healthcare facilities and units standardize care and quality, reduce costs, improve effectiveness and decrease prolonged waits. The current study is carried out in an emergency department of a university hospital to understand the patient flow of the department with respect to the Fuzzy Critical Path Method (FCPM) and Fuzzy Program Evaluation Review Technique (FPERT). The reason for incorporating fuzzy sets is stemmed from that fuzzy numbers are more effective for high uncertainty processes as in emergency departments. Activities affecting patient flow through the ED are identified and project network is drawn. 1500 patients' data about the times of each activities are obtained from the observed ED. Findings through application of FCPM and FPERT, the expected time for completion of the project, the critical path and slack times are determined.
Keywords: Healthcare; emergency department; patient flow; fuzzy critical path method; fuzzy program evaluation review technique; Engineering